Social Responsibility of Islamic Boarding Schools in Indonesia and Thailand - Kadri, Kadri; jumarim; Asyari, Akhmad (JURNAL PENELITIAN KEISLAMAN, 2024)
This study focuses on exploring the social engagement experiences of Sangkhom Islam Wittaya School and Lenterahati Islamic Boarding School as a manifestation of their social responsibility in the surrounding communities. Using a qualitative case study approach, the research employed three data collection techniques: in-depth interviews, observation, and document analysis, followed by qualitative analysis. The findings indicate that both institutions share similarities in the content and procedures of their social programs. These include regular programs in religious education, economic empowerment, healthcare, and basic infrastructure improvement, as well as their proactive involvement in disaster relief as part of their incidental programs. The community has expressed positive appreciation for the social programs implemented by both Sangkhom Islam Wittaya School and Lenterahati Islamic Boarding School, with a strong desire for the continuation of such initiatives. This study underscores the ability of these pesantren to adapt and align with public expectations within mutually beneficial collaborations